Effect of Biogas Slurry Fertilizer on Dynamics of Soil Consistency and Tillage Power Requirement - Cicilia Candra Palupi; Ngadisih Ngadisih; Joko Nugroho Wahyu Karyadi; Rose Tirtalistyani; Muhammad Heikal Ismail; Hanggar Ganara Mawandha (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2022)
Biogas slurry (BS) is a waste used as an organic fertilizer that could improve soil properties. This study was aimed to explore the dynamic of soil consistency and tillage power requirement due to BS fertilizer. Soil consistency and tillage power requirement were analyzed by the liquid (LL), plastic (PL), and adhesive (AL) limits, plasticity index (PI), workability range (WR), and liquidity index (LI). The study was conducted with incubation time and the BS type factors that include control (K), liquid BS (P1), and solid BS (P2). The incubation time factors comprised 2 (I1), 4 (I2), 6 (I3), 8 (I4), 10 (I5), and 12 weeks incubation (I6). The ANOVA test showed that BS fertilizer significantly affected LL, PL, AL, PI, and LI but did not significantly impact WR. The liquid BS fertilizer decreased LL and PI by 2%, increased LI 0.022, and decreased tillage power requirement by 1 horse power (HP). The solid BS, increased LL and PL 3%, PL 3% and AL 2%, while LI decreased by 0.074. The mathematic modeling with a first-order kinetic model was acceptable to describe soil consistency and tillage power requirement (R2>80% and X2<X2 table). The rate of AL for K, P1, and P2 were -0.022/day, -0.032/day, and -0.049/day, respectively. The minus is symbol of decreasing rate. The rate of WR for K, P1, and P2 were 0.024/day, 0.046/day, and 0.079/day, respectively. The form of BS fertilizer (liquid, solid) has changed the soil consistency which in turn has an impact on tillage power requirement.